Cultural Influences on Hispanic Mother–Daughter Communication About Sex. (May 2022) - Matsuda, Yui; DeBastiani, Summer D.; Thalasinos, Roxana D.; Ferranti, Dina; Norris, Anne E.; De Santis, Joseph P.
Introduction: Hispanic adolescents are at high risk of engaging in sexual risk-taking behaviors. Parent–child communication protects against such behaviors. Among Hispanic families, it is critical to explore how cultural characteristics influence mothers–daughter communication about sex. The purpose of this qualitative study was to understand how cultural values influence mothers' communication about sex with their early adolescent Hispanic daughters. Methodology: Twenty-one Hispanic mothers of seventh-grade daughters participated in this focus group study. Directed content analysis was used to analyze the data. Results: Four Hispanic cultural values ( familismo, machismo, marianismo, and respeto ) and how each value influences mother–daughter communication about sex were identified. While mothers want to protect their daughters, there are multiple cultural norms that made it challenging for them to have critical conversations. Discussion: The study informs researchers and clinicians how to facilitate parent–child conversations about sex and to equip parents to teach their children how to avoid engaging in sexual risk-taking behaviors.